2022
DOI: 10.1177/11206721221125004
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes of non-diffractive extended-depth-of-focus and enhanced monofocal intraocular lenses: A case-control study

Abstract: Objective To compare the visual outcomes of a non-diffractive extended-depth-of-focus (EDoF) intraocular lens (IOL) with an enhanced monofocal IOL. Methods We evaluated 76 eyes from 38 patients who had undergone bilateral cataract surgery with implantation of either an EDoF IOL (AcrySof IQ Vivity, n = 40 eyes) or an enhanced monofocal IOL (Tecnis Eyhance, n = 36 eyes). Objective refraction, monocular and binocular uncorrected and corrected distance visual acuity (UDVA, CDVA), uncorrected and distance-corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Bova et al [44], Nanavaty et al [39], Corbelli et al [49], Lopes et al [40], Steinmüller et al [17], Auffarth et al [45], Ucar et al [37], Kang et al [41], Unsal et al [38], Cinar et al [42], Huh et al [28], Yangzes et al [36], Eguileor et al [43], Mencucci et al [3], Garzón et al [46] the Tecnis Eyhance [31,32], and the optical quality studies that included both, enhanced monofocals and EDoF lenses, showed a higher depth of focus range with poorer distance optical quality for EDoF lenses in comparison to enhanced monofocals [25,27]. These laboratory results were in agreement with clinical evidence of studies including enhanced monofocals and EDoF lenses, demonstrating a higher range of focus and better DCNVA for the latter [33][34][35]49]. Interestingly, no significant differences were reported for visual acuities at intermediate vision [33][34][35].…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Bova et al [44], Nanavaty et al [39], Corbelli et al [49], Lopes et al [40], Steinmüller et al [17], Auffarth et al [45], Ucar et al [37], Kang et al [41], Unsal et al [38], Cinar et al [42], Huh et al [28], Yangzes et al [36], Eguileor et al [43], Mencucci et al [3], Garzón et al [46] the Tecnis Eyhance [31,32], and the optical quality studies that included both, enhanced monofocals and EDoF lenses, showed a higher depth of focus range with poorer distance optical quality for EDoF lenses in comparison to enhanced monofocals [25,27]. These laboratory results were in agreement with clinical evidence of studies including enhanced monofocals and EDoF lenses, demonstrating a higher range of focus and better DCNVA for the latter [33][34][35]49]. Interestingly, no significant differences were reported for visual acuities at intermediate vision [33][34][35].…”
Section: Discussionsupporting
confidence: 62%
“…General agreement was reported about a higher depth of focus range for EDOF lenses and statistically significant differences only at near vision [33][34][35]49]. Despite of the higher range of the depth of focus showed in the defocus curve and the statistically significant differences at near, no significant differences were reported for visual acuities at intermediate vision [33][34][35]. The comparison with the standard monofocals is presented in the next section.…”
Section: Clinical Studiesmentioning
confidence: 68%
See 3 more Smart Citations